A Török Birodalom balkáni területi rendszere - Csüllög, Gábor; Gulyás, László (Közép-Európai Közlemények, 2014)
The imperial areas were born in the European peripheries and main points of migration. They built on major European migration zones and they permanently possessed the important migration intersections. Their expansion and relation mainly reduces the number of the minor states, while their break-up, their fall or their recess helped in the growth. Their interest was to entirely governand possess active and opened migration zones. They operated and ruled their inner borders by interests of the becoming local provinces. By the end of the 15th century, the Ottoman organization annexed much of the earlier states in the Balkans and built a very effective imperial structure. In the middle of the 16th century, it extended its rule as well on the Hungarian Kingdom. The transformation of the Ottoman Empire took place slowly. After the big conquering era, which ended in the 17th century, various problems started to begin in the periphery of this empire in the 18th century. By the beginning of the 20th century, the Balkan wars resulted an entire volte-face and change against the Ottoman Empire.